The role of plasma D{u2013}dimer as prognostic marker in children with traumatic brain injury - Khaled Mohamed Abdeltwab Elsayed; Hala Gabr Metwally; Hala Mohamed Amin Fouad; John Rene Labib youssef (Cairo : Khaled Mohamed Abdeltwab Elsayed, 2014)
Objectives: To investigate the value of plasma D-dimer as a prognostic marker in severe traumatic brain injury in children and to compare the results of plasma D- dimer level in plasma and the clinical condition of the case and the results of its routine laboratory investigations. Methods: The study was carried out on 66 head trauma children 46 cases and 20 controls of both sexes, who admitted to pediatric intensive care unit in Alharam hospital in Giza. All children patients had full history, vital sign, general examination, complete neurological examination, GCS or PGCS, cranial CT scan, abdominal ultrasonography, full radiological studies, plasma D-dimer on admission, the 3rd day and at 14th day, INR, PT, APTT. on admission, the 3rd day and at 14th day, routine laboratory investigations on admission as CBC, CRP, Liver function test, Urea, Creatinine, Blood glucose, Na, K and Arterial blood gas analysis
Thesis (Ph.D.) - Cairo University - Faculty of Medicine- Department of Pediatrics
Issued also as CD
Keywords: Children; D-dimmer & markers; TBI